PERCEPTIONS OF PROFESSIONALS WORKING IN A UNIVERSITY HOSPITAL ABOUT THE PATIENT SAFETY CULTURE - Luana Silva Pereira Sátiro; Cláudia Cristiane Filgueira Martins Rodrigues; Manuela Pinto Tibúrcio; Patrícia Medeiros da Silva Oliveira; Pétala Tuani Cândido de Oliveira Salvador (Universidade Federal do Paraná, 2024)
Objective: to understand the perception of professionals working in a university hospital about the patient safety culture. Method: a descriptive study with a qualitative approach, carried out at a university hospital in the Brazilian Northeast region in January 2023. The participants were 56 professionals from the multidisciplinary, namely: nurses, pharmacists, physiotherapists, speech therapists, physicians, psychologists and nursing technicians. The data were obtained through semi-structured interviews. The text content was subjected to lexicographic analysis and against the current and relevant literature. Results: five classes were analyzed: Perceptions about patient safety and the safety culture; Actions to strengthen patient safety; Perceptions about the work of the Patient Safety Center; Contributions to strengthening the safety culture; and Professional performance in patient safety. Final considerations: the patient safety culture in the hospital has been on a promising path. The study can direct interventions that strengthen the patient safety culture.